2009
DOI: 10.1055/s-0029-1225401
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of Physicians' Knowledge of, Participation in, and Attitudes toward Newborn Hearing Screening Programs

Abstract: Physicians play a vital and important role in newborn hearing screening programs (NHSPs) and early hearing detection and intervention programs (EHDIPs). The information that physicians convey to parents of infants suspected of having hearing loss and the enthusiasm with which they make referrals for audiological services can greatly affect whether children are seen in a timely manner or are lost to follow-up and the perceptions of parents and others of these programs, which ultimately contributes to their over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 10 publications
(67 reference statements)
1
3
0
1
Order By: Relevance
“…This response rate was in line with several earlier studies that have unfortunately shown that physicians are rather notorious for having low compliance for replying to nonmedical, healthrelated surveys (e.g., Cartwright, 1978;McDonald, 1993;Sibbald et al, 1994;Asch et al, 1997;Templeton et al, 1997;Kaner et al, 1998;Pirotta et al, 1999;Cummings et al, 2001;Danhauer et al, 2006;Hocking et al, 2006;Danhauer et al, 2009;Mathews et al, 2009). Response rates for Peds and family physicians responding to questionnaires about newborn hearing screening programs have ranged from about 16 to 85% (Johnson et al, 2009a). Considerably higher response rates have been obtained for physician-to-physician surveys.…”
Section: Response Ratesupporting
confidence: 84%
See 1 more Smart Citation
“…This response rate was in line with several earlier studies that have unfortunately shown that physicians are rather notorious for having low compliance for replying to nonmedical, healthrelated surveys (e.g., Cartwright, 1978;McDonald, 1993;Sibbald et al, 1994;Asch et al, 1997;Templeton et al, 1997;Kaner et al, 1998;Pirotta et al, 1999;Cummings et al, 2001;Danhauer et al, 2006;Hocking et al, 2006;Danhauer et al, 2009;Mathews et al, 2009). Response rates for Peds and family physicians responding to questionnaires about newborn hearing screening programs have ranged from about 16 to 85% (Johnson et al, 2009a). Considerably higher response rates have been obtained for physician-to-physician surveys.…”
Section: Response Ratesupporting
confidence: 84%
“…Surveys have been shown to be a good way of obtaining information from physicians about areas of interest to audiologists (e.g., Danhauer et al, 2006Danhauer et al, , 2009Johnson et al, 2008Johnson et al, , 2009aJohnson et al, , 2009b. Therefore, the purposes of this study were to develop and administer a questionnaire to physicians in the United States that would provide information about (1) how Peds practice for AOM relative to the AAP/AAFP guideline and (2) what they believe about, and how they practice for, prevention of AOM in children.…”
mentioning
confidence: 99%
“…Others have reported similar findings for postal surveys, but rates as low as 11% have been documented for questionnaires distributed electronically to physicians. 33,34 Further, the results of a recent systematic review of the literature pertaining to physicians' knowledge of, participation in, and attitudes toward NHPS 35 revealed a wide range of response rates for national (16 to 44%), state (24 to 52%), and local (85 to 100%) samples. Interestingly, physicians are not the only ones to produce low survey return rates.…”
Section: Response Rate and Demographicsmentioning
confidence: 99%
“…About 95% of the physicians in the Danhauer et al 9 national study and 100% of the Peds in their local survey 5 responded similarly. Certainly, it is important for infants to be retested after medical treatment, but the results of the systematic review of Johnson and colleagues 35 indicated that many pediatricians did not even receive the initial NHSP results on their patients, which reflects a breakdown in the follow-up process that needs to be improved.…”
Section: Importance Of Audiologic Reevaluationmentioning
confidence: 99%
“…Los resultados de la investigación demuestran la conciencia existente entre la mayoría de los pediatras sobre la detección e intervención temprana de la hipoacusia. Resultados similares han sido reportados en la literatura sobre la concientización, conductas y actitudes de profesionales de la salud sobre programas de tamizaje auditivo universal, diagnóstico e intervención temprana de la hipoacusia 21,22,27,28,33 .…”
Section: Discussionunclassified